Synthesis and NMR studies of malonyl-linked glycoconjugates of N-(2-aminoethyl)glycine. Building blocks for the construction of combinatorial glycopeptide libraries - Nörrlinger, Markus; Hafner, Sven; Ziegler, Thomas (Beilstein Journal of Organic Chemistry, 2016)
Four glycoconjugate building blocks for the construction of combinatorial PNA like glycopeptide libraries were prepared in 75–79% yield by condensing tert-butyl N-[2-(N-9-fluorenylmethoxycarbonylamino)ethyl]glycinate (AEG) 5 with 3-oxo-3-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosylamino)- (6a), 3-oxo-3-(β-D-galactopyranosylamino)- (6b), 3-oxo-3-(2-acetamido-2-deoxy-3,4,6-tetra-O-acetyl-β-D-glucopyranosylamino)- (6c) and 3-oxo-3-(2-acetamido-2-deoxy-3,4,6-tetra-O-acetyl-β-D-galactopyranosylamino)propanoic acid (6d), respectively. The resulting AEG glycoconjugates 1a–d were converted into the corresponding free acids 2a–d in 97–98% yield by treatment with aqueous formic acid. The Fmoc group of compound 1c was removed and the intermediate amine 9 was condensed with 2a to afford the corresponding glycosylated AEG dipeptide 4 in 58% yield. All glycoconjugate building blocks showed the presence of cis and trans rotamers. Compounds 1a, 1b and 4 were subjected to temperature dependent 1H NMR spectroscopy in order to determine the coalescence temperature which resulted in calculated rotation barriers of 17.9–18.3 kcal/mol for the rotamers.
Keywords: amino acids; carbohydrates; glycoconjugates; glycopeptides; N-(2-aminoethyl)glycine